On Centralizing and Strong Commutativity Preserving Maps of Semiprime Rings - Gölbaşı, Ö.; Huang, Shuliang; Koç, E. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We study some properties of centralizing and strong commutativity preserving maps of semiprime rings.